Designing context-specific physical activity interventions for English primary schools: key learning from a four-month rapid ethnography - Robert Walker; Danielle House; Simona Kent-Saisch; Alice Porter; Ruth Salway; Lydia Emm-Collison; Michael Beets; David Revalds Lubans; Frank de Vocht; Russell Jago (BMC Public Health)
Abstract Background Physical activity is essential for children’s health. Primary schools offer an opportunity to equitably promote physical activity. However, school-based interventions have been shown to have little to no effect, potentially due to a lack of consideration of school heterogeneity. This study reports on a rapid ethnography study that was used to capture insights into English primary schools physical activity. The data are intended to inform the design of a context-specific intervention to improve pupil physical activity. Methods Three researchers conducted a four-month rapid ethnography study within three primary schools in Bristol, UK, between March and July 2024. Several methods were used: observations (n = 80), interviews (n = 26), photo elicitation with pupils (n = 4 activities, total 22 pupils), collection of documentary data (i.e. pupil demographics, school policies, etc.), informal conversations, and field notes. Reflexive thematic analysis was used to analyse the data. Results Each school measured success in physical activity differently, such as increased opportunities, personal development, or broader curriculum attainment. Across all schools levels of pupil physical activity varied across physical activity opportunities in the school day, with breaktimes most active, PE lessons focused on fundamental skills, and active clubs providing quality but not fully inclusive opportunities. Furthermore, across all schools different school communities consistently had different goals and needs for physical activity: senior leaders were focused on how physical activity can support broader school-level strategies (e.g. academic achievement and student wellbeing); teachers were concerned with how physical activity can fit in and around curriculum pressures; and pupils wanted fun and engaging activities. Not all physical activities were feasible across settings, emphasising the need for tailored strategies. And differences in Parent Teacher Association (PTA) funding impacted resources and opportunities for pupil physical activity. These various areas of convergence and difference across the schools suggest strategies for intervention development. Conclusion This study underscores the importance of context-specific approaches to promoting physical activity in primary schools. Context-specific intervention design should closely consider school context to ensure strategies are appropriate. Intervention designs should also include steps to understand different stakeholder goals, PTA funding disparities, and the appropriate areas of physical activity to target.